LEGACY OF TRUST (Editors: Daniel Greenberg and Mimsy Sadofsky) - Teitelbaum, Kenneth (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1993)
Daniel Greenberg and Mimsy Sadofsky (Editors). LEGACY OF TRUST: Life after the Sudbury Valley School experience. Framingham, MA: Sudbury Valley School Press, 1992.